# 6+2(3j-2)=4(1+j)

## Simple and best practice solution for 6+2(3j-2)=4(1+j) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6+2(3j-2)=4(1+j) equation:

Simplifying
6 + 2(3j + -2) = 4(1 + j)

Reorder the terms:
6 + 2(-2 + 3j) = 4(1 + j)
6 + (-2 * 2 + 3j * 2) = 4(1 + j)
6 + (-4 + 6j) = 4(1 + j)

Combine like terms: 6 + -4 = 2
2 + 6j = 4(1 + j)
2 + 6j = (1 * 4 + j * 4)
2 + 6j = (4 + 4j)

Solving
2 + 6j = 4 + 4j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-4j' to each side of the equation.
2 + 6j + -4j = 4 + 4j + -4j

Combine like terms: 6j + -4j = 2j
2 + 2j = 4 + 4j + -4j

Combine like terms: 4j + -4j = 0
2 + 2j = 4 + 0
2 + 2j = 4

Add '-2' to each side of the equation.
2 + -2 + 2j = 4 + -2

Combine like terms: 2 + -2 = 0
0 + 2j = 4 + -2
2j = 4 + -2

Combine like terms: 4 + -2 = 2
2j = 2

Divide each side by '2'.
j = 1

Simplifying
j = 1`